Himsa and Ahimsa in the Bhagavad Gita - Khatri, Tilak Bahadur (Cognition, 2019)
This research article deals with the question of himsa and ahimsa mentioned in the Bhagavad Gita. The study has its relevance to understand the Gita’s teaching on himsa and ahimsa. The research problem is that whether the Gita advocates himsa or ahimsa. The research approach (methodology) adopted for this study is the textual analysis of the Gita’s related verses along with the review-based analysis of the views on himsa and ahimsa expressed by the Gita’s commentators Bankim Chandra Chattopdyaya, Lokamanya Bal Gangadhar Tilak, Mahatma Gandhi and Aurobindo Ghosh. The study reveals that the Gita talks about ahimsa while mentioning the good traits of a Godlike person but the text basically focuses on the justified himsa as essential and obligatory in dealing with the evil persons of the imperfect human society.